2015
DOI: 10.5559/di.24.4.01
|View full text |Cite
|
Sign up to set email alerts
|

Domain, Gender and Age Differences in the Creative Behavior of Children

Abstract: Izvorni znanstveni rad Primljeno: 15. 7. 2015. This study focused on the domain, gender and age differences in the creative behavior of children. The questions on creativity model building were raised because of the significant implications of creativity for education and curricular development, as well as the improvement of creative teaching and teaching to develop creativity in children at the primary school level. The study participants were children aged 8-15, as well as prospective primary school teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Regarding the final cluster, a teacher's creativity lies not in performing as an artist, musician, inventor or researcher, but in creating learning environments that foster curiosity, bold ideas, risk taking, interaction and independence of thought, also recognizing, encouraging and evaluating each individual's progression and creativity (Baer, 2013), and is linked to students' creativity (Chan & Yuen, 2014). Implicit theories of general creativity in teachers are partially domain-specific, skewed towards the arts, as well as communication, entertainment, grooming, or play, and away from mathematics (Rački, Katalenić, & Gregorović, 2015), but are tied to knowledge acquisition (Rački, 2015). Creativity in teaching, that is, finding or inventing ways on how to achieve the planned educational goals in an optimal way, is also considered one of the prerequisites for advancement in teacher vocational status in the Republic of Croatia (Pravilnik o napredovanju učitelja i nastavnika u osnovnom i srednjem školstvu, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the final cluster, a teacher's creativity lies not in performing as an artist, musician, inventor or researcher, but in creating learning environments that foster curiosity, bold ideas, risk taking, interaction and independence of thought, also recognizing, encouraging and evaluating each individual's progression and creativity (Baer, 2013), and is linked to students' creativity (Chan & Yuen, 2014). Implicit theories of general creativity in teachers are partially domain-specific, skewed towards the arts, as well as communication, entertainment, grooming, or play, and away from mathematics (Rački, Katalenić, & Gregorović, 2015), but are tied to knowledge acquisition (Rački, 2015). Creativity in teaching, that is, finding or inventing ways on how to achieve the planned educational goals in an optimal way, is also considered one of the prerequisites for advancement in teacher vocational status in the Republic of Croatia (Pravilnik o napredovanju učitelja i nastavnika u osnovnom i srednjem školstvu, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Kreativnost se ogleda ne samo u kreiranju okruženja već i cjelokupnoga višegodišnjega procesa odgoja i obrazovanja, didaktičkih materijala, obrazovnih sadržaja i svega ostaloga, što najbolje znaju sami učitelji. Važno je samo naglasiti da su implicitne teorije učitelja o tome što predstavlja kreativnost djelomično područno specifične i snažnije usmjerene prema interpretaciji kreativnosti preko umjetnosti, komunikacije, zabave, osobne njege i igre, ali ne i preko matematike (Rački, Katalenić, i Gregorović, 2015), premda općenito upućuju na povezanost kreativnosti i sustavnoga usvajanja znanja (Rački, 2015), što je ključno. Ne iznenađuje da je kreativnost u poučavanju, tj.…”
Section: Raspravaunclassified
“…Recent research has pointed to creativity's domain specificity (e.g., Baer, 2010;Baer, 2015) or content specificity (e.g., Hu, Jia, Plucker, & Shan, 2016;Tyagi, 2016). An exploratory study by Rački (2015) examined creative behavior in children aged 8-15 and concluded that it is useful to distinguish three types of creative behavior: everyday creativity (including writing and storytelling), artistic creativity (including drawing), and scientific creativity. That study found that approximately 20% of children were gifted with only one creativity type, 5.6% were gifted with two types of creativity, and 5.5% were gifted in all three areas of creativity, i.e.…”
Section: Talent and Creativity In Preschoolers: A Pilot Studymentioning
confidence: 99%
“…Ten percent of the studied pool is presented in full in Table 3, mostly covering creativity in language, as one of the creativity microdomains represented in the behaviour pool. The collection, refinement and exploration of creative behaviours is an ongoing project, and the behavioural features of a sample of 50 (see Rački, 2015a) and 21 creative behaviours (see Rački, Bakota, & Flegar, 2015) have previously been discussed. Behaviours were prepared in two forms for participants to rate -as cards and a questionnaire-given in one or the other form to the participant groups.…”
Section: Brought To You By | Mit Librariesmentioning
confidence: 99%
“…To elaborate on this definition, creativity in children and adolescents in this study is defined as the a) observable, manifest, socially acceptable behaviour consensually described as creative in a given social context, b) result of the interaction of abilities, knowledge, traits, task commitment and social influences, c) process at the end of which a person can potentially produce an observable original product (Rački, 2015a;2015b;Rački, Bakota, & Flegar, 2015). As such, this definition puts the focus on the process (i.e.…”
Section: Introductionmentioning
confidence: 99%